Understanding and Perception of University Librarians on Knowledge Management (KM) and Its Implementation in University Libraries in India: A Study - Rao, S. Sudarshan (DESIDOC Journal of Library & Information Technology, 2016)
The paper defines Knowledge Management (KM) and enumerates its purposes, advantages and explains its application in libraries. It is the original research work conducted on 50 University librarians in India to find out their perception and understanding on KM and its implementation in universities / university libraries. The major findings of the study are: KM is more of information intensive activity than the information technology based one; large majority(70.0%) of the university librarians possess high level of understanding and knowledge on KM, which in fact, is a prerequisite for implementation of KM in the institutions or libraries; KM enhances the performance of libraries; Non-availability of required library professionals with IT skills and training is the major constraint in implementation of KM in academic institutions.